Physicochemical properties of Alisma starch - Han, Fenxia; Wang, Yongqiang; Zhang, Hao; Zhang, Sheng (Frontiers in Nutrition, 2025)
IntroductionAlisma starch (AS) from Alismatis Rhizoma has potential applications but has been less studied compared to common starches like corn starch (CS) and potato starch (PS).MethodsWe used scanning electron microscopy, X-ray diffraction, and rapid visco analysis to study the granule morphology, crystal structure, pasting properties, freeze -thaw stability, solubility, swelling degree, and gel strength of AS, CS, and PS.ResultsAS has a lower starch content but higher amylose content than CS and PS. It has a smaller particle size and is A-type starch. Its pasting temperature and trough viscosity are higher, and its freeze -thaw stability is intermediate. Gel strength increases with concentration and shows no significant difference between 10% AS and 12% PS.DiscussionAS has good heat resistance, shear resistance, and gel strength, indicating potential for high-temperature processed foods. Future research should focus on its heat resistance mechanism and broader applications.